Perancangan Website E-Commerce Berbasis Mobile-First-Design untuk Optimalisasi Efisiensi Layanan di Apotek Mumtaz Husada - Louisyana, Novia Marsheila (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2025)
The digitization of the healthcare sector has driven the development of e-commerce to enhance pharmacy service efficiency. Mumtaz Husada Pharmacy faces the issue of long queues during peak hours, which reduces customer satisfaction. This study aims to design a Mobile-First e-commerce website using the Waterfall method to optimize service efficiency at the pharmacy. The Mobile-First design ensures an optimal user experience on mobile devices, while the Waterfall method facilitates structured system development through stages of requirement analysis, design, implementation, testing, and maintenance. The results show that the e-commerce platform effectively reduces customer waiting times through features like online prescription ordering and scheduled pickups. The system also includes product management, transactions, and sales reporting to enhance operational efficiency. Laravel 11 and TailwindCSS support the development of a responsive interface and robust backend logic. The results is that a Mobile-First e-commerce website is an effective solution for minimizing queues, improving efficiency, and increasing customer satisfaction at Mumtaz Husada Pharmacy.